EKSISTENSI PASAR TRADISIONAL COMAL PADA ERA DISRUPSI 4.0 - Firdaus, Anbar Naurah; Lisfiana Lisfiana; Meilita Utami (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to examine the existence of the commercial market in the era of the industrial revolution 4.0, the research method uses qualitative field research. while in-depth interviews and library sources were used to obtain data. The research findings reveal that the awareness of traders is still low to develop their business and occupy a predetermined base place, as well as the low awareness of traders to pay user fees, and there are still markets whose activities are only on market days. While the trade development model strategy that can be done so that the comal traditional market is able to compete in the era of disruption 4.0 is by applying a price strategy, place or location strategy, promotion strategy, HR strategy, and process strategy, but Comal Market is still not optimal in making changes to innovation. facing the Industrial Revolution 4.0.